More Than Telling a Story: Transforming Data into Visually Shared Stories - Bongshin Lee; Riche, Nathalie Henry; Isenberg, Petra; Carpendale, Sheelagh (IEEE computer graphics and applications, 2015)
The authors take a closer look at how the visualization community has discussed visual storytelling and present a visual data storytelling process, incorporating steps involved in finding insights (explore data), turning these insights into a narrative (make a story), and communicating this narrative to an audience (tell a story). They also discuss opportunities for future research in visualization as a storytelling medium in the light of this broader process.